THEORETICAL AND METHODOLOGICAL PRINCIPLES OF RESEARCH AND FEATURES OF ENSURING FINANCIAL SECURITY OF THE SMALL ENTERPRISE SECTOR OF THE REGION - SHOPSKA, YULIYA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the study is to substantiate the theoretical and methodological foundations of the study and the features of financial security of the small business sector in the region. Scientific approaches to the essential interpretation of the concept of financial security of the state are generalized. The key characteristics of the theoretical and methodological foundations of financial security of the enterprise are given. The semantic specifics of the concept of economic security of the industry, sector of the national economy are revealed. On this basis, the theoretical and methodological foundations of the study of economic and financial security at different levels of management of economic development and established that the financial security of the small business sector is a characteristic: (1) the state of protection of its subjects from internal and external financial and economic challenges and threats, their financial security, financial and economic efficiency, strength and balance of financial condition, stability and solvency, trends in capitalization at the micro level and the financial system in general, ( 2) measures to realize the financial and economic interests of stakeholders in this sector, (3) the ability of the state to ensure guarantees of financial security and stability of the sector, especially at the regional level. The internal structure of financial security of the small business sector of the region is determined. The scientific novelty of the research results is the further development of theoretical and methodological foundations of financial security research at the sectoral level by determining its internal structure (for the small business sector of the region), consisting of components: (1) ability to markets and rights), (2) sustainability, efficiency, protection (against risks and threats, as well as financial and economic efficiency of management and investment), (3) development (ability to maintain a sustainable trajectory of improving the key financial and economic characteristics of both entities and the sector as a whole). The structural components of the financial security of the small business sector of the region are resource, financial and economic, investment, monetary, insurance and debt.